Aramid reinforced polyimide aerogel composites with high‐mechanical strength for thermal insulation material. (26th January 2023) - Liu, Tuo; Liang, Fuwei; Chen, Shun; Zhang, Ping; Qian, Kun; Xu, Yang; Guo, Wenwen
Abstract: Polyimide (PI) aerogels have attracted extensive attention in the field of building insulation due to their low‐thermal conductivity, excellent thermal stability, and great flame retardancy. However, poor mechanical strength was the main factor which restrict their extensive applications. Herein, we report a simple strategy to prepare thermal insulating aramid/PI aerogel composites with high mechanical strength as well as flame retardancy through mold‐forming and freeze‐drying methods. A series of lightweight aramid felt reinforced PI aerogel composites were prepared by interfacial adhesion between aramid fiber and PI aerogel, and the most striking sample PI‐3 displayed favorable comprehensive performance, including good tensile property (8.88 MPa), bursting performance (299 N), thermal insulation property (0.0341 W/m·K), thermal stability and self‐extinguishing behavior. This strategy can be applied to many types of organic aerogel materials that used in the aspects of insulation and thermal protection in extreme environments.